AMPK activation by ozone therapy inhibits tissue factor‐triggered intestinal ischemia and ameliorates chemotherapeutic enteritis. Issue 9 (9th August 2020) - Yu, Qingqing; Yang, Xing; Zhang, Chen; Zhang, Xiaotao; Wang, Chaoyu; Chen, Lu; Liu, Xiaolin; Gu, Yufeng; He, Xueming; Hu, Liang; Liu, Wen‐Tao; Li, Yan
Abstract: Chemotherapeutic enteritis is a major dose‐limiting adverse reaction to chemotherapy, with few effective drugs in clinic. Intestinal ischemic injury plays prominent role in chemotherapeutic enteritis clinically. However, mechanism is not clear. In this article, irinotecan (CPT‐11) was used to establish chemotherapeutic enteritis mice model. Western blotting, gelatin zymography, immunohistochemistry (IHC), Laser Doppler flowmetry (LDF) were used to detect the pathogenesis of ischemia‐hypoxia injury. CPT‐11 increased levels of tissue factor (TF) both in the blood and in intestines, and decreased the intestinal blood flow in mice. Interestingly, the elevation of TF in the blood displayed "double‐peak, " which was consistent with the intestinal mucosal "double‐strike" injury trend. Intestinal microthrombus and mixed thrombus formation were detectable in chemotherapeutic enteritis. Furthermore, ozone therapy relieved chemotherapeutic enteritis in mice. Ozone inhibited TF expression induced by CPT‐11 via activating AMPK/SOCS3, and effectively ameliorated the intestinal mucosal injury in mice. Moreover, ozone autotransfusion therapy effectively attenuated chemotherapeutic enteritis and the blood hypercoagulability in patients. For the first time, we proposed that TF‐induced thrombotic intestinal ischemic injury is a core trigger pathological mechanism of chemotherapeutic enteritis, and provided a new treatment strategy, ozone therapy, to suppress TF expression and treat chemotherapeutic enteritis.